1917 in the History of the Petrograd Synodal Printing House - Anatoly Kashevarov (Вестник Свято-Филаретовского института, 2019)
The article studies the situation in the Petrograd Synodal Printing House after the February revolution of 1917. To protect the workers’ rights, a committee of elders was formed in the printing house. Instead of the assigned functions of a labour union organization, the committee started establishing control over production and finances without any consent of the administration. This disorganised the production process and led to the breakdown of the financial and economic part. On the order of the Minister of Confessions A. V. Kartashev of 4 August 1917, the Commission on printing was formed. It suggested measures for managing the catastrophic situation in the Synodal printing house. However, these measures could have been implemented only if the general political situation in the country had changed.